FAKTOR-FAKTOR PENILAIAN KINERJA KEUANGAN PADA PT. SINAR RODA UTAMA - Sari, Putri Ratna (JEBI | Jurnal Ekonomi Bisnis Indonesia, 2018)
The purpose of this study is to find out how financial ratio analysis to assess the financialperformance of PT. Main Wheel Rays in terms of liquidity ratios, solvency ratios, and profitabilityratios using secondary data. The research method used is descriptive quantitative and independentvariables, namely the company's financial performance measured by several sub variablesincluding liquidity ratios, solvency ratios, and profitability ratios. The results of the research are theanalysis of the ratio of liquidity, solvency, and profitability to assess the financial performance of PT.Main Wheel Rays seen from the liquidity ratio of the company's financial performance are in goodcondition, but too much cash is not used. When viewed from the solvency ratio, the company'sfinancial performance is in a bad condition, because the debt ratio continues to increase. Whenviewed from the profitability ratio, the company's financial performance is in good condition, butmust continue to increase profits.